Abrupt Climate Change around 4 ka BP： Role of the Thermohaline Circulation as Indicated by a GCM Experiment - 王绍武 周天军 蔡静宁 朱锦红 谢志辉 龚道溢 (Advances in atmospheric sciences, 2004)
A great deal of palaeoenvironmental and palaeoclimatic evidence suggests that a predominant tem-perature drop and an aridification occurred at ca. 4.0 ka BP. Palaeoclimate studies in China support thisdedution. The collapse of ancient civilizations at ca. 4.0 ka BP in the Nile Valley and Mesopotamia hasbeen attributed to climate-induced aridification. A widespread alternation of the ancient cultures was alsofound in China at ca. 4.0 ka BP in concert with the collapse of the civilizations in the Old World. Palaeo-climatic studies indicate that the abrupt climate change at 4.0 ka BP is one of the realizations of the coldphase in millennial scale climate oscillations, which may be related to the modulation of the ThermohalineCirculation (THC) over the Atlantic Ocean. Therefore, this study conducts a numerical experiment ofa GCM with SST forcing to simulate the impact of the weakening of the THC. Results show a drop intemperature from North Europe, the northern middle East Asia, and northern East Asia and a significantreduction of precipitation in East Africa, the Middle East, the Indian Peninsula, and the Yellow RiverValley. This seems to support the idea that coldness and aridification at ca. 4.0 ka BP was caused by theweakening of the THC.